2002
DOI: 10.1111/j.0014-3820.2002.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

How Can Sex Ratio Distorters Reach Extreme Prevalences? Male-Killing Wolbachia Are Not Suppressed and Have Near-Perfect Vertical Transmission Efficiency in Acraea Encedon

Abstract: Maternally transmitted bacteria that kill male hosts early in their development are found in many insects. These parasites typically infect 1-30% of wild females, but in a few species of insects, prevalences exceed 95%. We investigated one such case in the butterfly Acraea encedon, which is infected with a male-killing Wolbachia bacterium. We measured three key parameters that affect the prevalence of the parasite: transmission efficiency, rate of survival of infected males, and the direct cost of infection. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 23 publications
(31 reference statements)
0
47
2
Order By: Relevance
“…Further, it should also be noted that although our study is unique in its combination of extreme bias and historical data, other studies have also failed to find resistance to selfish genetic elements in natural populations Fertility is given as percentage of eggs laid showing some sign of development, with interquartile range in parentheses. (19)(20)(21)(22). Most pertinently, there is the case of sex-ratio meiotic drive in Drosophila pseudoobscura.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it should also be noted that although our study is unique in its combination of extreme bias and historical data, other studies have also failed to find resistance to selfish genetic elements in natural populations Fertility is given as percentage of eggs laid showing some sign of development, with interquartile range in parentheses. (19)(20)(21)(22). Most pertinently, there is the case of sex-ratio meiotic drive in Drosophila pseudoobscura.…”
Section: Discussionmentioning
confidence: 99%
“…This is because first, linkage of all newly arisen alleles in infected females to the male-killing element is complete or at least very high. Linkage here corresponds to the vertical transmission rate of the male-killing bacteria, for which quantity values in the range of 0.8-1 have been reported in natural and laboratory populations of various insect species (Hurst and Majerus 1993 and references therein;Jiggins et al 2002;Dyer and Jaenike 2004). Second, despite their being strongly deleterious to nuclear alleles, male-killing bacteria carry a drive and can be stably maintained in populations at high frequencies (Dyer and Jaenike 2004;Dyson and Hurst 2004).…”
Section: Imperfect Transmissionmentioning
confidence: 97%
“…populations infected with male-killing bacteria (e.g., Jiggins et al 2002;Dyson and Hurst 2004). Moreover, we assume that the prevalence of the male-killing bacteria and the population sex ratio remain constant over the time frame under consideration.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This "best" malekiller does not seem to occur among those that infect coccinellids. In none is the vertical transmission efficiency perfect (Table 1), in A. decempunctata and Cheilomenes sexmaculatus, infected males sometimes survive to adulthood Majerus, 2003a), and in all coccinellid cases studied (but not in one butterfly species (Jiggins et al, 2002)), male-killers have been shown to have direct costs on infected females (Matsuka et al, 1975;Hurst et al, 1994;Majerus, 2003a). Why is this the case?…”
Section: Selection On Host Nuclear Genomes: Vertical Transmission Sumentioning
confidence: 99%